2017
DOI: 10.1007/s11746-017-2978-y
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherols, Tocotrienols and Carotenoids in Kernel Oils Recovered from 15 Apricot (Prunus armeniaca L.) Genotypes

Abstract: We studied the content of tocopherols, tocotrienols and carotenoids in oil extracted from the kernels of 15 apricot (Prunus armeniaca L.) genotypes and the associated oil yield of the studied samples. The oil yield in apricot kernels was in a wide range of 27.2-61.4% (w/w) dry weight basis. For each class of studied compounds (tocochromanols and carotenoids), a three-fold difference was found between the lowest and the highest content (78.8-258.5 and 0.15-0.53 mg/100 g of oil, respectively). γ-Tocopherol accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…The impact of Japanese quince genotype on the seed oil yield was not studied previously, nevertheless, a similar oil extractability from Japanese quince seeds, as obtained in the present study, by the ultrasound‐assisted and cold‐press extraction methods were reported previously . The importance of the genotype of plants belonging to the Rosaceae family for potential oil extraction from seeds and kernels has been underlined as an important economic factor …”
Section: Resultssupporting
confidence: 86%
“…The impact of Japanese quince genotype on the seed oil yield was not studied previously, nevertheless, a similar oil extractability from Japanese quince seeds, as obtained in the present study, by the ultrasound‐assisted and cold‐press extraction methods were reported previously . The importance of the genotype of plants belonging to the Rosaceae family for potential oil extraction from seeds and kernels has been underlined as an important economic factor …”
Section: Resultssupporting
confidence: 86%
“…There is no significant influence of the debitterizing treatment on the contents of oils in the apricot kernels (data not shown), so only the composition of the fatty acids was investigated in this research. Although some other bioactive compounds such as tocopherols, sterols, squalene, and carotenoids are also included in the oils of apricot kernels, yet the contents are significantly lower than those of sugars, proteins, and phenols (Górnaś et al, ; Rudzińska, Górnaś, Raczyk, & Soliven, ); therefore, these lipophilic compounds will be investigated in future. The profiles of fatty acids in the apricot kernels were conducted by the GC–MS; one of the typical total ion chromatograms is presented in Figure , and the main fatty acids compositions and their relative contents are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…α‐T, δ‐T, γ‐T3, α‐T3, and β‐T constituted small percentages: 4.2, 2.0, 1.1, 0.4, and 0.1%, respectively. A predominance of γ‐T (on the levels 90% of total tocopherols) was reported also in the seed oils recovered from plants such as watermelon ( C. lanatus ), pomegranate ( Punica granatum ), gooseberry (Górnaś et al, ), pear ( Pyrus communis ) (Górnaś et al, ), and apricot ( Prunus armeniaca ) (Górnaś et al, ).…”
Section: Beneficial Componentsmentioning
confidence: 91%